Design of a wide-band transition between coaxial probe and parallel-plate waveguide - Xu, Zhipeng (2016)
With development of complex microwave system, transitions between coaxial probe and parallel-plate waveguide are very essential. The main objective of this project is to make the overall reflection coefficient, S11 better than -10dB within a wide bandwidth of 1GHz to 10 GHz. The major goal for this final year project is to design a wide-band transition between coaxial probe and parallel-plate waveguide. The design has been completed and simulated with widely used software High Frequency Structure Simulator (HFSS). This wide-band transition between coaxial probe and parallel-plate waveguide has been fabricated to demonstrate and verify the design concept. The simulation and measurement result will be shown in this report. The first stage of this final year project was to learn the basic knowledge and theory. Some researching had been done to help understand the impact of each parameter. The second stage was focusing on how to use the software to build up the transition and simulate by changing various parameters. The final stage was to find company to fabricate and test the design with comparing measured results with simulated results.